Jeřábová kočka - Šponar, Pavel (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2009)
Bakalářská práce se zabývá návrhem pojezdového ústrojí jeřábové kočky (elektromotoru a převodovky) a kontrolním výpočtem na rozběh. Cílem je navrhnout pojezdové kolo s uložením, proto se musí také vhodně navrhnout normalizované součásti. Pevnostní výpočty pojezdového kola, ložiska a hřídele (statické a dynamické namáhání).

Bachelor thesis deals with a project of the travelling mechanism of the travelling crab (electric motor and gear-box) and check calculation for starting. The aim of this work is to design a travelling wheel with save, therefore it is necessary to design the suitable normalized components. The solidity calculations of the travelling wheel, the bearing and shaft ( static and dynamin straining).
Travelling Crab
Keywords: jeřábová kočka; pojezdové kolo; hřídel; ložisko; elektromotor; převodovka; travelling crab; travelling wheel; shaft; bearing; electric motor; gear-box